2010
DOI: 10.1007/s00167-010-1293-z
|View full text |Cite
|
Sign up to set email alerts
|

Posterior shoulder instability: current concepts review

Abstract: For surgical treatment to be successful, the instability must be attributable to mechanical factors that can be modified by surgery. Because of better knowledge of the pathology, a more specific surgery can be performed. This lesion-specific surgery has improved clinical results compared to non-anatomic stability procedures, particularly when that surgery has been performed arthroscopically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 64 publications
(114 reference statements)
0
41
0
2
Order By: Relevance
“…Patients with recurrent instability typically recall a single event that initiated the process, followed by repeated episodes of apprehension or instability with positional progression from extremes of motion to midrange motion. 4,5,8 Standard radiographs (anteroposterior, axillary lateral) may appear normal, but careful examination can detect subtle abnormalities that can predispose to posterior instability, such as glenoid hypoplasia, posterior rim deficiency, and glenoid retroversion. Magnetic resonance imaging is useful to detect capsuloligamentous pathology and articular cartilage loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with recurrent instability typically recall a single event that initiated the process, followed by repeated episodes of apprehension or instability with positional progression from extremes of motion to midrange motion. 4,5,8 Standard radiographs (anteroposterior, axillary lateral) may appear normal, but careful examination can detect subtle abnormalities that can predispose to posterior instability, such as glenoid hypoplasia, posterior rim deficiency, and glenoid retroversion. Magnetic resonance imaging is useful to detect capsuloligamentous pathology and articular cartilage loss.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional reconstructions with humeral head subtraction can improve the accuracy of quantifying the extent of glenoid bone loss. 1,[4][5][6] It is well recognized that anterior glenoid bone loss is a significant contributor to recurrent anterior instability if the defect amounts to greater than 25% of the articular surface. The current gold-standard treatment for glenoid bone loss in the setting of recurrent instability is a coracoid transfer with the Bristow-Latarjet procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The posterior Bankart procedure with reinsertion of the dorsal labrum and capsular shift has been effective in post-traumatic cases without hyperlaxity, as well as in cases of recurrent posterior subluxation. 10 Fronek et al 6 reported a 91% success rate after posterior shoulder stabilization in a series of 11 patients treated with open capsulorrhaphy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Commonly, soft-tissue reconstructions are performed in the case of capsulolabral lesions and normal bony anatomy, but especially in the presence of traumatic posterior bony Bankart lesions, glenoid erosion, or posterior glenoid dysplasia, open bone grafting techniques have been reported [3][4][5][6][7] ( Fig 1, Table 1). Even in the absence of osseous deficiency, many authors have performed posterior bone block procedures to reduce the high rate of recurrent instability reported after soft-tissue repairs.…”
mentioning
confidence: 99%